2009
DOI: 10.1007/s11740-008-0148-7
|View full text |Cite
|
Sign up to set email alerts
|

A 3D transient model of keyhole and melt pool dynamics in laser beam welding applied to the joining of zinc coated sheets

Abstract: In order to get a deeper understanding of laser beam welding, a process model was developed at the Chair of Manufacturing Technology. It is based on the continuity equation, the equation of heat conduction and the NavierStokes equation. The model includes effects of Fresnel absorption, vapor pressure, surface tension, melting and evaporation enthalpy and energy loss due to evaporating material. This paper presents the results of a three-dimensional, transient finite volume simulation of a laser beam deep penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(56 citation statements)
references
References 13 publications
1
48
0
Order By: Relevance
“…The same discussion applies also to boundary condition of pressure in numerical simulations of a keyhole welding process, which have already been reported by several groups [16,17,33]. The result of our study highlights the importance of imposing the ambient atmospheric pressure P amb to non-evaporating surfaces, although this boundary condition was not clearly described in these papers.…”
Section: Weldingsupporting
confidence: 79%
“…The same discussion applies also to boundary condition of pressure in numerical simulations of a keyhole welding process, which have already been reported by several groups [16,17,33]. The result of our study highlights the importance of imposing the ambient atmospheric pressure P amb to non-evaporating surfaces, although this boundary condition was not clearly described in these papers.…”
Section: Weldingsupporting
confidence: 79%
“…Over the last two decades, literature has been reported on sophisticated modeling approaches [7][8][9][10][11][12] and experimental techniques [13][14][15][16][17][18] to study the dynamics of the keyhole phenomena during high power density fusion welding technologies, such as laser welding. From a modeling perspective, the interface deformation that leads to keyhole formation during the laser welding has been studied intensively using various numerical techniques, including a volume-of-fluid approach [13,14] and a level set method. [9] Recently, Courtois et al [9] have proposed a level set approach and included the influence of the electromagnetic field to accurately capture the energy reflection inside the keyhole.…”
mentioning
confidence: 99%
“…In the numerical simulation presented by Geiger et al [28] it was shown that as the gap at the interface between two uncoated sheets welded in an overlap configuration increases to 0.05-0.1 mm, the liquid metal on the keyhole front wall tends to separate; i.e. a channel opens connecting the interface gap to the keyhole.…”
Section: Zinc Vapour Evacuation Through the Keyhole Front Wallmentioning
confidence: 99%